EFFECT OF KADAWA IRRIGATION PROJECT ON EMPLOYMENT OPPORTUNITY AMONG FARMERS IN KURA AND GARUN-MALAM LOCAL GOVERNMENT AREAS OF KANO STATE (2000-2015) - Yusuf, Bashir; Idris, Musa; A. Yusuf, Hamza (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2020)
This study examined the effect of Kadawa Irrigation Project on the creation of employment opportunities among beneficiaries in Kura and Garun-Malam Local Government Areas of Kano State from 2000-2015. The study adopted survey research approach, where data was generated from both primary and secondary sources. Primary data were sourced through the administration of questionnaires and conduct of interviews. Secondary data, on the other hand, were derived from reports and official documents. Ten Registered Farmers Associations (RFAs) was selected from 58 registered irrigation farmers in the study area. The RFAs have a population of 2000 members from which a sample of 322 was selected. Data were analyzed using descriptive statistical tools. Regression analysis was employed to test the hypothesis. It was revealed that Kadawa Irrigation project has a significant effect on providing employment opportunities among farmers in Kura and Garun-Malam Local Government Areas of Kano State. It was recommended among other things that, HJRBDA should intensify its effort towards increasing the land coverage for irrigation by increasing to 22,000 hectares as was originally designed to cover, this will increase the opportunities for more employment to the youth. More so, credit schemes on agriculture provided by the current administration should be extended to irrigation farmers in the area to establish small, medium, and large processing and agrochemical industries in the area which is hoped to increase employment opportunities and the income levels of irrigation farmers